Prevalence of diabetic foot ulcers and assessment of foot care knowledge and practice among patients attending diabetic clinic of a tertiary hospital of eastern India - Mitra, Satabdi; Majumdar, Kunal Kanti; Bhanja, Sushanta (International Journal Of Community Medicine And Public Health, 2023)
Background: Diabetic foot ulcer (DFU) is a dreaded complication holding huge health and socio-economic impacts and negative impacts on quality of life of individual, community and society as a whole yet carrying scope of preventive potential. The objectives were to find out the prevalence of diabetic foot ulcers and to assess gap in knowledge, foot care practices and their determinants. Methods: A cross-sectional study was conducted over three months among 310 diabetic outpatients of a medical college of an eastern Indian state. Data were collected with a validated questionnaire containing socio-demographics, clinical and behavioral factors, foot care knowledge and practice and SINBAD score was used for assessing diabetic ulcers. Results: Out of 310 participants, 44 (14.2%) had diabetic foot ulcer and 1/5th of them had SINBAD score ≥3 indicating severity. Knowledge level was poor among 245 (79.0%) and healthy foot habits were among only 70 (22.6%). Addiction, diabetes for ≥5 years, any associated non-communicable diseases, irregular treatment and follow-up care, unhealthy foot condition, improper foot wear, poor knowledge of the disease and unhealthy foot habits had significant association with occurrence of foot ulcers. Conclusions: Generation of awareness can bring about prevention of development of foot ulceration among diabetic patients and henceforth can avert risk of adverse consequences of it.